Psychological Impact of Covid-19 Pandemic on Health Care Workers of a Field Hospital in UN Peacekeeping Mission (Bangladesh Armed Forces Medical Journal, 2024)
Background: The Covid-19 pandemic has significantly affected the healthcare system worldwide as well as the psychological state of all. The objective of the current study was to assess the psychological conditions of the healthcare workers in Enhanced Level 1+ Hospital, Bouar, Central African Republic (CAR). This assessment can help in the guideline development and implication psychological interventions which in turn can improve the quality of life, working environment and decision-making capabilities of health care workers during widespread pandemic.Methods:  This descriptive cross-sectional study was conducted on 40 medical personnel working in Enhanced Level 1+ Hospital, Bouar, Central African Republic. The study was performed from June 2022 to August 2022. Assessment of psychological status of military healthcare providers was done by analyzing the results derived from the Mental health survey, Perceived Stress Scale (PSS-10), Generalized Anxiety Disorder scale (GAD-7) and Patient Health Questionnaire (PHQ-9). Hospital records were analyzed to assess the changes in workload.Results: The working hour increased significantly from Pre Covid to Post Covid period (1920±34.1 hours/week to 2120±67.3 hours/week) although the number of weekly patients in OPD and Emergency decreased slightly from 51.9 to 40.6. Elevated mental stress was observed during outbreak (average PSS-10 score in June 22 was 20.4 which reduced to 9.7 in August). The same pattern was observed in case of GAD-7 score (15.6 to 10.8) and PHQ-9 score (12.4 to 6.1). The percentage of concerns regarding Covid19 was high during the outbreak, 37/40 (92.5%), which decreased after wards to 18/40 (45%).Conclusion: The UN field hospitals are inadequate to support mass outbreak like COVID 19 in the context of both staff and medical supplies. During Covid 19 outbreak, sharp rise of workload and difficulties in restocking of essential medical items played a vital role in the mental state of the medical professionals. The field hospitals in UN peacekeeping missions require intensive effort especially on disaster and epidemic management during pre-deployment training. Moreover, reconsidering distribution of human resources in field hospitals is also required.Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 35-42